1979
DOI: 10.3186/jjphytopath.45.369
|View full text |Cite
|
Sign up to set email alerts
|

Back transmission of apple chlorotic leafspot virus (type strain) to apple and production of apple topworking disease symptoms in Maruba Kaido (Malus prunifolia Borkh. var. ringo Asami.

Abstract: Apple chlorotic leafspot virus (CLSV) type strain isolated from an apple tree was back-transmitted to 8-day-old apple seedlings by rub-inoculation with partially purified and highly purified inoculum.The back-transmitted isolates induced typical apple topworking disease symptoms on a clone of Maruba Kaido (Malus prunifolia Borkh. var. ringo Asami) infected with other latent viruses (including the Maruba CLSV strain) as well as on a virus-free clone.The back-transmitted isolates induced symptoms identical to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…It generally has proved difficult to inoculate fruit trees, including apple, with viruses by conventional methods such as sap inoculation and stem slashing (Yanase et al 1979;Muruganantham et al 2009;Yamagishi et al 2010). We had recently developed an efficient method by biolistic inoculation of the cotyledons of seeds just after germination with viral RNAs by particle bombardment (Yamagishi The results presented here showed that the Arabidopsis FT gene expressed by the ALSV vector could induce early flowering in apple seedlings.…”
Section: Discussionmentioning
confidence: 98%
“…It generally has proved difficult to inoculate fruit trees, including apple, with viruses by conventional methods such as sap inoculation and stem slashing (Yanase et al 1979;Muruganantham et al 2009;Yamagishi et al 2010). We had recently developed an efficient method by biolistic inoculation of the cotyledons of seeds just after germination with viral RNAs by particle bombardment (Yamagishi The results presented here showed that the Arabidopsis FT gene expressed by the ALSV vector could induce early flowering in apple seedlings.…”
Section: Discussionmentioning
confidence: 98%
“…pitting virus (ASPV) can cause top-working disease of apple and pear in sensitive rootstocks (Yanase et al 1979;Desvignes and Boyé 1989). In stone-fruit trees the virus leads to severe symptoms, including dark green sunken mottle in peach, rosette formation and graft incompatibility in apricot, pseudopox and bark split in plum, and bark split in cherry (Dunez et al 1972;Desvignes and Boyé 1989;Cieślińska et al 1995;Jelkmann and Kunze 1995).…”
mentioning
confidence: 98%
“…In contrast, only a few studies on virus vectors for VIGS in fruit tree species had been reported until recently, mainly because of the lack of efficient viral vectors. Furthermore, woody plants are usually more resistant to virus infections and the mechanical inoculation methods routinely used for herbaceous plants are not readily applicable to fruit tree species (Yamagishi et al, 2010;Yanase et al, 1979).…”
Section: Construction Of Alsv Vectorsmentioning
confidence: 99%